Analyzing Effective Strategies Utilized by Language Learning Platforms - Raj , Aparna (UICELL, 2023)
The aim of this paper is to explore digital platforms for language learning to improve the English speaking skills of homemakers in North Kerala. This paper reviews the effectiveness of a language learning websites, with a particular reference to ‘English House’ created in Kerala. English House aims to assist Malayali candidates in achieving Speaking fluency in English. They offer a comprehensive range of online and offline classes adapted to meet the individual needs of candidates. English House emphasizes the vital role of continuous language practice in skill acquisition, assesses candidates' knowledge levels, and designing modules through the help of trainers. The trainers use WhatsApp, a widely accessible digital platform for effective teaching practices, enabling candidates to practice language skills anywhere, fostering a flexible learning environment. The presence of dedicated training partners on WhatsApp keeps candidates engaged and interested, while customized language learning activities align with individual interests, creating a personalized and engaging learning experience. One-on-one sessions between trainers and trainees also foster emotional bonds, which are instrumental in language acquisition. These innovative approaches and tools can be smoothly integrated into traditional classroom environments to increase and enrich language teaching, providing a bridge between traditional and digital learning methods. Keywords: Digital Platform, WhatsApp, Language Learning, Homemakers